Uncovering the Relationship between Profitability and Firm Value: Are Interest Rates a Strengthener or a Hindrance? - Fadilla Lisfi Oktavia; Perdana Wahyu Santosa (Research of Economics and Business, 2026)
This study examines the influence of firm profitability on firm value, with interest rates as a moderating variable, and reviews the findings from an Islamic perspective. The research problem stems from inconsistencies in prior empirical findings regarding the effect of profitability indicators on firm value, as well as the role of macroeconomic factors, particularly interest rates, in strengthening or weakening this relationship. Therefore, the study aims to analyze the effects of profitability measured by Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) on firm value, and to test the moderating role of interest rates. The sample consists of 18 non-financial companies included in the LQ-45 Index and listed on the Indonesia Stock Exchange during 2017–2022, selected using purposive sampling. Data were collected from financial statements and analyzed using panel data regression. The results show that NPM has a negative but insignificant effect on firm value, while ROA has a significant negative effect. In contrast, ROE has a significant positive effect. Interest rates do not directly affect firm value but strengthen the relationship between profitability variables and firm value, indicating a moderating effect. These findings suggest investors prioritize equity efficiency.